2010
DOI: 10.1007/bf03403848
|View full text |Cite
|
Sign up to set email alerts
|

Examining Occupational Traumatic Brain Injury in Ontario

Abstract: raumatic brain injury (TBI) is a leading cause of death and disability worldwide. It is a very serious and often overlooked health care issue. Victims are often young, and survivors of TBI often live with devastating consequences, including temporary or permanent impairments, partial or total functional disability, psychosocial maladjustments and associated economic burdens. 1 Even mild injuries can have long-term consequences. 2 An examination of coroners' files in Ontario showed that approximately half of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 12 publications
8
41
1
Order By: Relevance
“…Unlike studies using trauma registry or death records,4 6 7 14 in which females accounted for <10% of wrTBI cases, over one-third (36.4%) of wrTBIs were sustained by females in our study. This is most comparable to an Ontario-based study, in which 42% of claims for wrTBI across a range of severity levels involved females 9. Additionally, in agreement with previous findings,4 10 14 30 we showed that males were at higher risk of wrTBI than females (RR 1.4).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Unlike studies using trauma registry or death records,4 6 7 14 in which females accounted for <10% of wrTBI cases, over one-third (36.4%) of wrTBIs were sustained by females in our study. This is most comparable to an Ontario-based study, in which 42% of claims for wrTBI across a range of severity levels involved females 9. Additionally, in agreement with previous findings,4 10 14 30 we showed that males were at higher risk of wrTBI than females (RR 1.4).…”
Section: Discussionsupporting
confidence: 91%
“…While male cases were concentrated in occupations or industries normally associated with physical labour and/or hazardous work conditions, most female cases occurred in service industries, such as healthcare and education. These findings are similar to those of the Ontario study,9 although direct comparisons are difficult due to differences in workforce composition, workers’ compensation systems and industry classifications. Moreover, consistent with a US study exploring gender differences in work-related injuries/illnesses,18 we found that males were at higher risk of wrTBI than females across most industry sectors.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations